Overcoming Animosities: History Issues and Japan’s Cooperation with Southeast Asia - Żakowski, Karol (Rethinking Asia in World Politics, 2023)
Although anti-Japanese sentiments in Southeast Asia initially remained strong after the Second World War, since the 1970s, Tokyo has managed to establish mutually beneficial cooperation with many Association of Southeast Asian Nations (ASEAN) countries. Cordial relations between Japan and Southeast Asian states contrasted with periodic reemergence of history issues between Japan and China or South Korea. This article examines the causes of this difference. It analyzes the international and domestic factors behind rapprochement between Japan and such states as Singapore, Malaysia, Indonesia, or Vietnam. It is argued that reconciliation with ASEAN countries was a part of Japan’s foreign policy strategy. Initially, it was aimed at promoting mutually beneficial trade through the Fukuda Doctrine, but over time, it started serving as one of the ways of containing and counterbalancing China’s rise in the region.